Characteristics of a cluster-randomized phase IV human papillomavirus vaccination effectiveness trial. Issue 10 (3rd March 2015) - Lehtinen, Matti; Apter, Dan; Baussano, Iacopo; Eriksson, Tiina; Natunen, Kari; Paavonen, Jorma; Vänskä, Simopekka; Bi, Dan; David, Marie-Pierre; Datta, Sanjoy; Struyf, Frank; Jenkins, David; et al.
Abstract High-risk human papillomaviruses (hrHPV) cause anogenital and oropharyngeal cancers. HPV-16/18 virus-like particle vaccine formulated with an AS04 adjuvant is very efficacious against hrHPV associated precancers but the herd effects of different vaccination scenarios are not known. Our cluster randomized trial (NCT00534638) assesses the overall and herd effects of vaccinating girls vs. girls and boys. In two school-years (2007–2008 and 2008–2009) we invited 80, 272 1992–1995 born early adolescents to a CRT in 33 communities a priori stratified by low, intermediate and high HPV-16/18 seroprevalence. In 11 Arm A communities 90% of participating girls and boys were assigned to receive HPV-16/18 vaccine, in 11 Arm B communities 90% of girls were assigned to receive HPV-16/18 vaccine – boys were assigned to receive hepatitis B-virus (HBV) vaccine, and in 11 Arm C communities all were assigned to receive HBV-vaccine. Prevalence of HPV in vaccinated and unvaccinated girls is studied at age 18.5 years. Recruitment resulted in equal enrolment of four birth cohorts (born 1992–1995) comprising altogether 32, 175 (40% response) early adolescents: 20, 514 girls (50.5–53.0% response by arm) and 11, 661 boys (21.9–31.6%% response by arm). At the age of 15 years, 79.3% of the vaccinees completed a questionnaire. Among them >98% were living at, and during the week-ends 1.3–1.6% stayed outside, the study site communities. Smoking habit and alcohol consumption were similar in the different trial arms, also mean-age of menarche (12.4 years) and 1st ejaculation (12.6 years), and sexual behaviour (among those <25%, who had had sexual debut) did not differ by arm: mean-age at the sexual debut 14.3 and 14.4 in girls and boys, and proportions of those with multiple (≥5) life-time sexual partners (6.5–7.5%) at the age of 15 years. Uniform residential, life-style and sexual behaviour characteristics indicate successful randomization/enrolment of the CRT. Our CRT will verify modelled predictions on up to 31% herd effect of vaccinating both girls and boys with moderate vaccine coverage – quantifying overall effectiveness of different strategies which will soon guide how to implement HPV vaccination.